FINANCIAL WELLBEING, PEACE OF MIND, HOPE, AND SUBJECTIVE HAPPINESS AS PREDICTORS OF GINHAWA AMONG FILIPINO ADULTS - Lucañas, Mhaigne Ahne V.; Celespara, Kristina; Dadivo, Jhelsie Joy L.; Regoso, Alyanna Ivy C.; Rungduin, Darwin C. (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
For decades, the prerogative that the western system of knowledge is more accurate in explaining the Filipino experience perpetuates the death of its culture. The epistemic violence resulted in psychology as science for the people to not deliver its purpose to the people i.e., to improve lives. Thus, the study examines financial well-being, peace of mind, subjective happiness, and hope as predictors of ginhawa (wellness). Using the Structural Equation Model, we developed a culturally appropriate model to understand Filipino wellness. This study hypothesized that (1) there are different levels of peace of mind, financial well-being, subjective happiness, and hope among Filipino adults and (2) financial well-being, subjective happiness, hope, and peace of mind predicts ginhawa. The proposed model was tested on N=366 adult Filipino citizens (63.39% female, 36.07% male, 0.55% intersex). Results find that financial well-being needs subjective happiness and peace of mind to predict ginhawa while peace of mind and subjective happiness explains how hope predicts ginhawa. Financial well-being plays a huge role in predicting ginhawa, having financial security and freedom proceeds to having life satisfaction, including happiness, peace of mind, and hope where Filipino perceived having a maginhawang buhay. Thus, findings of the study contribute to the present and future initiatives of the Philippines by implementing programs and therapeutic approaches for Filipinos.